1999
DOI: 10.1016/s0014-5793(99)00231-8
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate prevents prooxidant effects of urate in oxidation of human low density lipoprotein

Abstract: Uric acid and ascorbic acid are important low molecular weight antioxidants in plasma. Their interactions and combined effect on Cu P+ -catalysed oxidation of human low density lipoprotein were studied in vitro. It was found that uric acid alone becomes strongly prooxidant whenever it is added to low density lipoprotein shortly after the start of oxidation (conditional prooxidant). Ascorbic acid, which is present in human plasma at much lower concentrations (20^60 W WM) than urate (300^400 W WM), is in itself … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 17 publications
6
85
2
1
Order By: Relevance
“…21 Despite this, several studies have demonstrated that uric acid can be prooxidative and may generate free radicals. [22][23][24][25] The ability to activate p38 MAPK, NF-kB, and AP-1, as well as to increase MCP-1 expression, is consistent with an oxidantdriven pathway. 26,27 In conclusion, we have found that uric acid can induce inflammatory pathways in rat VSMCs in vitro, with activation of p38 MAPK, NF-B, and AP-1 and increased expression of COX-2 and MCP-1.…”
Section: Discussionmentioning
confidence: 56%
“…21 Despite this, several studies have demonstrated that uric acid can be prooxidative and may generate free radicals. [22][23][24][25] The ability to activate p38 MAPK, NF-kB, and AP-1, as well as to increase MCP-1 expression, is consistent with an oxidantdriven pathway. 26,27 In conclusion, we have found that uric acid can induce inflammatory pathways in rat VSMCs in vitro, with activation of p38 MAPK, NF-B, and AP-1 and increased expression of COX-2 and MCP-1.…”
Section: Discussionmentioning
confidence: 56%
“…This can be explained on several accounts. It has been suggested that 60% of FRAP activity is contributed by uric acid and hyperuricemia as part of the metabolic syndrome [2,[42][43][44] may be responsible for higher FRAP in the NAFLD group. The increase in FRAP levels may occur as a compensatory phenomenon in NA-FLD patients to protect against OS.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have revealed similar properties in other common antioxidants, including flavonoids [30], nonflavonoid phenols [36], cysteine [37,38], and urate [39][40][41]. The effects of ascorbate are further complicated by the fact that dehydroascorbate, the product of its two-electron oxidation, can itself act as both a pro-oxidant and an antioxidant toward LDL [24,26,35,42].…”
Section: Introductionmentioning
confidence: 99%